Recent Trends in Power Quality Improvement Using Custom Power Devices and Its Performance Analysis - et. al., V.Vinothkumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Power quality is the measure of any deviation from the standard voltage level and nominal frequency values. A power quality problem seen from the customer's point of view is defined as any power problem expressed in voltage, current or frequency deviations that result from a power failure or equipment customer misoperation. This paper presents the working, configurations, and important functions of each custom power device. Because many of these devices can reduce power quality problems, researchers are focusing on new technologies using power electronics-based concepts. The power electronics application to the power distribution system for the benefit of a customer or a customer group is called custom power. The custom power devices like Distribution Static compensator (DSTATCOM), the Dynamic voltage restorer (DVR) and the Unified Power Quality Conditioner (UPQC) are discussed for this work. Detailed results are provided to evaluate the working of each device as a potential custom power solution using MATLAB simulink.